Treatment Results of Residual-Angles Operated Esotropia by the Method of Z-Shaped Marginal Myotomy - A. S. Gavrilyuk; A. V. Artamonova; A. O. Ivanova; I. V. Maksimov; L. N. Zubareva (Oftalʹmologiâ)
Purpose. Analysis of the results of weakening of previously operated internal rectus muscle by the method of Z-shaped marginal myotomy.Patients and methods. The study included 87 children with an initially large-angle of strabismus. Children age — from 2 to 14 years (average age — 9.09 ± 0.78 years). The initial strabismus angle was from 30° to 60° according to Girschberg (average angle — 45.7° ± 2.3°). All children underwent a staged surgical treatment — recession of the internal rectus muscle and resection of the external rectus muscle in both eyes. The residual deviation angle after two stages of surgical treatment ranged from 6° to 10° (on average up to 9.1° ± 0.75°) according to Girschberg. All patients underwent a Z-shaped marginal myotomy on the operated internal rectus muscle. The follow-up period after surgery ranged from 1 year to 5 years.Results. A satisfactory anatomical result (orthotropy) was achieved in 91 % of cases (79 children), hypocorrection in 9 % of cases (8 children), hypercorrection — 0 %. In 8 patients with hypocorrection, after 6–8 months, the fourth stage of surgical treatment was performed with the method of Z-shaped marginal myotomy of the internal rectus muscle in the paired eye, after which orthotropy was achieved.Conclusion. An analysis of the surgical treatment results of operated esotropia have showed that the method of Z-shaped marginal myotomy makes it possible to weaken the tone of the previously operated internal rectus muscle with minimal trauma. Using the method of Z-shaped marginal myotomy in the treatment of residual-angle strabismus, orthotropy is achieved while preserving the biomechanics of the oculomotor muscles — the internal rectus muscle remains in the plane of its functional action. At initially large-angle of strabismus, conducting a Z-shaped marginal myotomy of the internal rectus muscle after stepwise surgical interventions on the horizontal rectus muscles of both eyes can be recommended as a modern, reliable and effective method of surgical treatment of residual-angle of strabismus, which allows to achieve the planned functional and cosmetic result.